TP10.2.1Lessons Learnt in the Management of Acute Appendicitis During the Sars Covid-19 [Cv 19] First Wave. (28th October 2021) - Ngugi, Josephine; Patel, Nikhita; Al-Whouhayb, Maitham; Mathur, Pawan
Abstract: Aims: To evaluate the impact of CV19 on surgical technique and patient outcome in management of acute appendicitis during the 1 st wave. Method: Data was collected on patients presenting with appendicitis to ED. Group A: Jan-March 2020, pre COVID and Group B: April-June 2020: peri COVID Results: There was no difference in sex, age and length of stay between groups. In group A [n = 194], 88% had lap appendicectomy vs Group B [n = 98], 97% had an open operation. Group A had a complication rate of 6% [wound infection] with no readmissions. Group B had 31% complication rate [intra-abdominal collection, bleeding, and ileus] requiring readmission. 685 surgical patients attended ED in the first half of 2020 of which 4 % had an appendicectomy. However the method of surgical access in the 1 st wave significantly impacted on patient outcome, resource and re-admission rates. Conclusion: In our study open appendicectomy undertaken due to concerns around COVID transmission during laparoscopic surgery during the 1 st wave, increased rates of complications and readmission thus raising hospital costs and chances of COVID 19 infection in these patients. As a result of this and due to greater confidence in laparoscopic surgery as a whole we have returned to undertaking laparoscopic appendicectomy in the current wave. Further analysis is underway assessing the impact of COVID on all emergency operations undertaken in the 1 st wave.